A review on socio-demographic factors influencing physical activities / Nurain Mohd Talmizi, Nor Eeda Ali and Suharto Teriman - Mohd Talmizi, Nurain; Ali, Nor Eeda; Teriman, Suharto (Universiti Teknologi MARA, Perak, 2021)
Engagement in physical activity has been demonstrated by various studies as one of the ways to curb the prevalence of chronic disease that is related to deaths globally. Knowledge of how socio-demographic factors do influence physical activity can have a significant social and economic impact, both in the economic and family context. Thus, this article reviewed the existing literature on the nexus between socio-demographic factors and engagement in physical activity. Almost all evidences from the studies indicate that men tend to participate more frequently in physical activities than women. Individuals with higher educational and income background, the unmarried and the younger ones have high probability of engaging in physical activity. Identifying some of the socio-cultural factors that impede engagement of women in physical activities in most developing countries is recommended as it is a step towards enabling women to inculcate the habit of regular participation in physical activities. Besides, by improving an individual's education one can enhance knowledge on the relevance of physical activity on health and human wellbeing.